A phase II study of elacytarabine in combination with idarubicin and of human equilibrative nucleoside transporter 1 expression in patients with acute myeloid leukemia and persistent blasts after the first induction course. Issue 9 (September 2014) - Rizzieri, David; Vey, Norbert; Thomas, Xavier; Huguet-Rigal, Françoise; Schlenk, Richard F.; Krauter, Jürgen; Kindler, Thomas; Gjertsen, Bjørn Tore; Blau, Igor Wolfgang; Jacobsen, Tove Flem; Johansen, Malin; Bergeland, Trygve; et al.
Abstract Unlike cytarabine, cellular entry of Elacytarabine, the elaidic acid ester derivative of cytarabine, is independent of the human equilibrative nucleoside transporter 1 (hENT1). This phase II study tested whether the hENT1 blast expression level can be used as a predictive marker for cytarabine response and if the efficacy of elacytarabine is independent of hENT1 expression. A total of 51 patients with acute myeloid leukemia (AML) induction failure were given elacytarabine–idarubicin as a second induction course. The hENT1 expression level was analyzed prior to first induction and/or prior to treatment with elacytarabine. The overall response rate (ORR) was 41% and the safety profile was manageable. There is a trend suggesting that hENT1 expression influences response to cytarabine, but not sufficient to support it as a biomarker for guiding treatment. Further, we conclude that the activity of elacytarabine is not significantly predicted by the hENT1 expression level.